2023
DOI: 10.1182/bloodadvances.2022007456
|View full text |Cite
|
Sign up to set email alerts
|

Host metabolome predicts the severity and onset of acute toxicities induced by CAR T-cell therapy

Abstract: Anti-CD19 chimeric antigen receptor (CAR) T-cell therapy is a highly effective treatment option for patients with relapsed/refractory large B cell lymphoma (r/r LBCL). However, widespread use is deterred by development of clinically significant acute inflammatory toxicities, including cytokine release syndrome (CRS) and immune effector cell associated neurotoxicity syndrome (ICANS), that induce significant morbidity and require close monitoring. Identification of host biochemical signatures that predict the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Lastly, the mechanisms underlying the differential toxicities reported for patients treated with Benda vs those treated with Flu/Cy are still unclear. Previous studies demonstrated that cytokines and serum metabolites are associated with systemic inflammation 14 , 15 and that chemotherapy can directly modify their circulating levels. 16 , 17 However, the direct contribution of LD in generating a cytokine and metabolic environment promoting the onset of CART-related toxicities has, to our knowledge, not been investigated to date.…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, the mechanisms underlying the differential toxicities reported for patients treated with Benda vs those treated with Flu/Cy are still unclear. Previous studies demonstrated that cytokines and serum metabolites are associated with systemic inflammation 14 , 15 and that chemotherapy can directly modify their circulating levels. 16 , 17 However, the direct contribution of LD in generating a cytokine and metabolic environment promoting the onset of CART-related toxicities has, to our knowledge, not been investigated to date.…”
Section: Introductionmentioning
confidence: 99%
“…Pennisi et al modified the Endothelial Activation and Stress Index (EASIX) score, used to predict outcomes in HSCT, by replacing creatinine with CRP to create the formula lactate dehydrogenase (LDH) x CRP/platelet count and found good association between development of severe CRS and ICANS and this modified score [ 47 ]. In a unique approach, Jalota et al explored pretreatment metabolic parameters and found that higher glucose, lower glutamine, and lower cholesterol were associated with earlier onset CRS [ 48 ]. While several of these boast remarkable specificities/sensitivities, their utility in prospective risk stratification is yet to be determined.…”
Section: Cytokine Release Syndromementioning
confidence: 99%